Preparation and structural stability of ordered nanocomposites: opal matrix - lead titanates; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Samoylovich M. I.; Mkrtchan (Mkrtchyan) A. R. Alpik Rafaelovich; Belyanin А. F.; Bagdasaryan S. A.; Kiziridi A. A. Aydana Abayevna (2016, 2016)
Title screen